Bibliography reference book on the history of neo-populist parties in Russia (the first third of the 20th century) - A. Y. Suslov (Библиосфера)
The concept and structure of a bibliographical reference book on the history of neo-populism and neo-populist parties in the history of Russia in the 1st third of the XXth century. Summarized is the experience of work on gathering information, the importance of the problem is characterized.